S-layer proteins as immune players: Tales from pathogenic and non-pathogenic bacteria - Assandri, Matías Hernán (2023)
In bacteria, as in other microorganisms, surface compounds interact with different pattern recognition receptors expressed by host cells, which usually triggers a variety of cellular responses that result in immunomodulation. The S-layer is a two-dimensional macromolecular crystalline structure formed by (glyco)-protein subunits that covers the surface of many species of Bacteria and almost all Archaea. In Bacteria, the presence of S-layer has been described in both pathogenic and non-pathogenic strains. As surface components, special attention deserves the role that S-layer proteins (SLPs) play in the interaction of bacterial cells with humoral and cellular components of the immune system. In this sense, some differences can be predicted between pathogenic and non-pathogenic bacteria. In the first group, the S-layer constitutes an important virulence factor, which in turn makes it a potential therapeutic target. For the other group, the growing interest to understand the mechanisms of action of commensal microbiota and probiotic strains has prompted the studies of the role of the S-layer in the interaction between the host immune cells and bacteria bearing this surface structure. In this review, we aim to summarize the main latest reports and the perspectives of bacterial SLPs as immune players, focusing on those from pathogenic and commensal/probiotic most studied species.